STRATEGI PENGEMBANGAN DAN PENGELOLAAN POTENSI TUK MUDAL SEBAGAI DESTINASI WISATA MLALUI KEGIATAN BUDIDAYA LOBSTER (Cherax lorents) DI KABUPATEN TEGAL - Narto; Suyono; Hartanti, Ninik Umi (Universitas Pancasakti Tegal, 2023)
Cempaka Village is located in Bumijawa District, Tegal Regency. In geographically, Cempaka Village is at the foot of Mount Selamet with an area of 8000 ha and is located at an altitude of 500 - 650 meters above sea level. A population of 7904 people divided into 3,685 men and 4,219 women is very strategic and has a lot of natural potential that should be able to increase the productivity of its citizens. The natural potential in Cempaka Village has been utilized by the Tourism Awareness Group (Pokdarwis) so that in 2017 the village The village was made one of the Tourism Villages of Tegal Regency with the destinations of Slumpring Market, Tuk Mudal, and Bukit Bulak Cempaka. However, even though the village has become a Tourism Village, there are still many Pokdarwis members who have not committed to the program because the results have not met daily needs. This is supported by the Village Government in conserving springs on agricultural land. As is known, there are 7 springs in one area that irrigate 160 hectares of rice fields. He was worried that the spring would die, and in the end, together with local youths, he carried out maintenance and construction of a dam so that mud from outside would not enter. As an effort to maximize the assistance, the method used in this research is qualitative with SWOT analysis and Process Hierarchy Analysis (AHP). Based on the results of the calculation of the value in the IFAS matrix, the total value of internal factors is 4.17 and EFAS is obtained the total value of external factors is 3.07. Mudal As a tourist destination through lobster cultivation activities (Cherax lorents) in Cempaka Village, Bumijawa District, Tegal Regency. Thus, the development strategy that needs to be carried out. Improvement of cultivation technology can be done by strengthening the marketing network strategy based on technical maintenance and cultivation technology which can be recommended is development based on cultivated commodities and intensive application of cultivation technology.